Caminhos e possibilidades na educação infantil: valorizando as culturas da infância - Guedes, Carolline Rodrigues [UNESP]; Lima, José Milton de [UNESP]; Lima, Márcia Regina Canhoto de [UNESP]; Romero, Luiz Rogério [UNESP]; Watanabe, Denise [UNESP]; Prado, Janaina Bolssone do [UNESP]; Furlan, Susana Angelin [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The present project takes as object of study the cultures of childhood in the context of early childhood education. Is based on the Sociology of childhood, which sees children as subjects and culture producers interpretative. The project takes place in two early childhood institutions-I and II, of the city of Álvares Machado-SP, serving a total of 220 children in the age group of the 05 03 years and 10 teachers. Assumes that, in reality, there are teachers who favor in their practices, only content related to linguistic and logical-mathematical literacy, i.e. secundarizam important elements in the formation of the child, especially the playful, imaginative and interactive. The methodology used is action research that seeks the close relationship between theory and practice, University and schools of basic education. As a result, it can be seen that, through the playful and imaginative activities, the educational environment is more attractive, enjoyable and meaningful for children and close interpersonal interactions among peers, with the teachers and the project team.

O presente projeto assume como objeto de estudo as culturas da infância no contexto da Educação Infantil. Fundamenta-se na Sociologia da Infância, que concebe as crianças como sujeitos interpretativos e produtores de cultura. O projeto acontece em duas instituições de Educação Infantil – I e II, da cidade de Álvares Machado - SP, atendendo, no total, 220 crianças na faixa etária de 03 a 05 anos e 10 professoras. Parte do pressuposto de que, na realidade estudada, existem professores que privilegiam, em suas práticas, apenas conteúdos relacionados à alfabetização linguística e lógico-matemática, ou seja, secundarizam elementos importantes na formação da criança, destaque para o lúdico, o imaginativo e o interativo. A metodologia utilizada é a pesquisa-ação que busca a estreita relação entre teoria e prática, universidade e escolas da Educação Básica. Como resultados, constata-se que, através das atividades lúdicas e imaginativas, o ambiente educacional fica mais atraente, prazeroso e significativo para as crianças e estreita as interações interpessoais entre os pares, com as professoras e a equipe do projeto.
Keywords: Sociology of childhood; Imagination; Playfulness; Sociologia da infância; Imaginação; Ludicidade